Strain Rate Effects of Polymeric Foam Cores Under Compressive Loading - M. R. M., Rejab; N. M. Zuki, N. M.; M. M., Noor (2008)

(untitled)
Polymeric foams are widely used as core materials in various applications such as in cushioning, padding, insulating, structural use and buoyancy. This is because of its ability to provide high bending stiffness tied with lightweight in sandwich construction. The purpose of this paper is to investigate the strain rate effects to the polymeric foam cores under compression load. The case study included rigid polyurethane (PUR), low density polyethylene (LDPE) and polystyrene (PS) foam cores. In order to study the strain-rate dependence for these three different foams, compression tests based on the ASTM D 1621 were conducted over a range in strain rates of 0.0001 s-1 to 0.01 s-1 under the 50kN-Instron universal testing machine. From the compression data, the stress-strain curves were produced. The results from the tests show that when the strain rate is higher, the area under the plateau region increases and higher amount of energy can be absorbed. The results also shows that the collapse stresses of the foams increased linearly with the logarithm of the strain rate.